Hadith #3073 - Sunan Abi Dawud - Abdah bin Sulaiman al-Klabi عبدة بن سليمان الكلابي أبو محمد الكوفي; Hanad bin al-Sari bin Mus'ab هناد بن السري بن مصعب; Ibn Ishaq محمد بن إسحاق بن يسار‎; Ishaq bin Yasar إسحاق بن يسار (Sunan Abi Dawud)
The Prophet (ﷺ) said: If anyone brings barren land into cultivation, it belongs to him, and the unjust vein has no right.
Grade: Sahih